Boston Museum at 28 Tremont Street, ca. 1880-1900 - Unknown (Tufts Archival Research Center, 2005)
Elevated view south-southeast of the Boston Museum, located at 28 Tremont Street between Scollay Square to the northeast and School Street to the southwest. Signage and awnings adorn the facades of stores located on the first level of the museum building. The facade of the Boston Museum, which faces west-northwest, is adorned with street lights and wrought-iron railing. A horse-drawn carriage is parked on Tremont Street, and pedestrians are included in the photograph. Donated by Robert Severy. 9 3/4 x 7 9/16 Photographs